2003
DOI: 10.1074/jbc.m208930200
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Interactions with Membrane-bound Transporter Associated with Antigen Processing Proteins

Abstract: The transporter associated with antigen processing (TAP) contains two nucleotide-binding domains (NBD) in the TAP1 and TAP2 subunits. When expressed as individual subunits or domains, TAP1 and TAP2 NBD differ markedly in their nucleotide binding properties. We investigated whether the two nucleotide-binding sites of TAP1/TAP2 complexes also differed in their nucleotide binding properties. To facilitate electrophoretic separation of the subunits when in complex, we used TAP complexes in which one of the subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
7
22
1
Order By: Relevance
“…In summary, we concluded that these single site mutations do not influence ATP binding to TAP. This is in agreement with studies on single TAP subunits and TAP complexes, all showing similar affinities for ATP in the micromolar range (33).…”
Section: Single Site Mutants Of the C-loop-it Was Recentlysupporting
confidence: 80%
See 1 more Smart Citation
“…In summary, we concluded that these single site mutations do not influence ATP binding to TAP. This is in agreement with studies on single TAP subunits and TAP complexes, all showing similar affinities for ATP in the micromolar range (33).…”
Section: Single Site Mutants Of the C-loop-it Was Recentlysupporting
confidence: 80%
“…Accordingly, mutations in ATP-binding site I (formed by Walker A and B motifs of TAP1 and C-loop of TAP2) are tolerated to a certain extent, whereas TAP complexes with the same mutations in site II are inactive. These findings are in harmony with studies on TAP complexes containing Walker A mutations in TAP1 (site I), which are still able to transport peptides although with very low efficiency, whereas equivalent mutations at site II fully disrupt peptide translocation (15,33). Notably, all C-loop mutants are active in peptide and ATP binding, indicating that these mutations influence the ATPase activity of TAP.…”
Section: Discussionsupporting
confidence: 62%
“…However, at some stage during the transport cycle, TAP2 binds and hydrolyzes ATP, which is critical for driving conformational changes associated with transport [46] -TAP2 forms the main contacts to the ATP hydrolyzed in the consensus ATPase site [39]. While it has been suggested that TAP2 only displays a preference for ADP when isolated from TAP1 and that the physiological TAP1/2 heterodimer has no such nucleotide preferences [47], another possibility is that the nucleotide specificity of TAP2 is regulated during a transport cycle. Using chimeras between the TAP1 and TAP2 proteins, it was observed that a short stretch of amino acids near the C-terminus is responsible for the unique nucleotide specificities [48].…”
Section: Asymmetry In the Tap Atpase Sites Refines A Model For Peptidmentioning
confidence: 99%
“…The apparent dissociation constant of Mg•ATP of 90± 12 μM for TAPL was derived. This value is in the same range as that of other ABC transporters (Horn et al 2003;Lapinski et al 2003;Qu et al 2003). A lower K m(ATP) value than the K D for TAP indicates that the ATP-binding step is followed by intermediates before final hydrolysis occurs (Fersht 1997).…”
Section: Nucleotide-dependent Peptide Transportmentioning
confidence: 75%